Analisis Tingkatan Tanda dalam Karya Frida Kahlo "Self Potrait with Necklace of Thorn and The Humming Bird" - Ahda Yunia Sekar (JURNAL RUPA, 2017)
This paper is concering in visual text research on Frida Kahlo painting, tittled Self Potrait with Thorn Necklace and The Hummingbird. This research is focused in visual symbols which is building the subject matter in the work of Frida as denotation and connotation meaning. The research use qualitative descriptive methods to analyze the element of semiology based on Roland Barthes theory. In this research indicate that Frida painting, Self Potrait with Thorn Necklace and The Hummingbird, is a track record of Frida's life story in sharp and contrast visual language. Representing a sense of fear, sad and pain that she experienced in herself. Her marriage life with Diego Rivera which is ended up in divorce and the pain of being have the physical health problems in her life. The accident that she experienced as a teenager, make she could not have fertility womb like other women. In that circumstance, she thought that the power and freedom to be a woman constrained by the physical condition of the body. But that problems did not make Frida became very discouraged, it is reflected in her expression of optimism and a serious look on the possibilities that will occur in front of the eye.